ANALISIS PENGARUH INOVASI PRODUK, INOVASI LAYANAN DAN KUALITAS PELAYANAN TERHADAP KEPUASAN DAN LOYALITAS NASABAH - Antanegoro, RM Yordan; Sanusi, Fauzi; Surya, Djasuro (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2017)
This study aims to determine the influence of product innovation, service innovation and service quality to satisfaction and loyalty KKB BCA customer in Cilegon Branch. Using the explanatory survey, data were collected through questionnaires distributed to 135 respondents. Data were analyzed using descriptive statistical analysis and Structural Equation Model (SEM) testing through SmartPLS program version 2.0.3. From the data obtained, the result (1) Product innovation has a significant positive effect on customer satisfaction with value 31.6%; (2) Service innovation has a significant positive effect on customer satisfaction with value 54.7%; (3) The service quality has a significant positive effect on customer satisfaction with value 20.5%; (4) Product innovation has a significant positive effect on customer loyalty with value 78,1%; (5) Service quality does not affect customer loyalty with value 3,9%; (6) Customer satisfaction has a significant positive effect on customer loyalty with value 18,8%.